Activities of Cinnamaldehyde from Boswellia Serrata on MCF-7 Breast Cancer Cell Line - B.N., Poornima; Deeba, Farah (International Journal of Scientific Research in Biological Sciences, 2020)
Boswellia serrata also known as Indian frankincense is known for its medical practice for thousands of years. B. serrata is recognized for its anti-tumor and anti-inflammatory actions. Cinnamaldehyde is one of the common compounds derived from B. serrata from Methanolic extract (ME), Dichloromethanol extract (DME) and Hydrodistillate extracts. MCF-7 cell lines were tested to understand the effects of cinnamaldehyde on hemolysis, its cytotoxic effect, and antioxidant activity (Hydroxyl radical scavenging assay and Clonogenic Survival Assays). Cinnamaldehyde is a natural substance derived from B. serrata that is known for its anti-proliferative activity. The anti-proliferative effect of cinnamaldehyde was investigated to work out its mechanisms of inhibition of growth proliferation at the morphological level. 100?M of ME was found to be more efficient to deliver the expected results while deriving less inhibition coefficient when compared with 100?M of DME. The study reveals the mechanisms of the anti-proliferative activities of cinnamaldehyde in MCF-7 breast cell lines, and further emphasizes that cinnamaldehyde could be a safe and effective natural agent for the treatment of breast cancer. These studies indicate that Cinnamaldehyde could be a potential candidate for further studies related to chemo therapy for breast carcinoma